Вплив лазерного випромінювання на електретний стан в інтеркальованому кобальтом селеніді галію - Войтович, С. А.; Григорчак, І. І. (Eastern-European Journal of Enterprise Technologies, 2009)
The results of our investigation of intercalation compounds (<Co>xGaSe) indicate the existence of electron hopping transfer. The results of impedance spectroscopy and pyroelectric response evidence the efficiency of influence of pulsing laser irradiation on impurity energetic spectrum of intercalation compounds and their electret state as well